2015
DOI: 10.1056/nejmoa1507643
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab versus Docetaxel in Advanced Nonsquamous Non–Small-Cell Lung Cancer

Abstract: Background Options for patients with non-squamous non-small cell lung cancer (NSCLC) whose disease progresses after first-line chemotherapy are limited. This randomized, open-label, international phase 3 study evaluated efficacy and safety of nivolumab versus docetaxel in this patient population after failure of platinum doublet chemotherapy. Methods Patients were randomized to nivolumab 3 mg per kilogram every 2 weeks or docetaxel 75 mg per square meter every 3 weeks. The primary endpoint was overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

256
7,635
39
118

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 8,313 publications
(8,048 citation statements)
references
References 22 publications
256
7,635
39
118
Order By: Relevance
“…The interaction between the immune system, tumor and the tumor microenvironment has been the focus of intense investigation—specifically the role of the PD‐1/PDL‐1 signaling axis,38 The efficacy of PD‐1 inhibition (i.e., nivolumab and pembrolizumab) as a monotherapy or in combination therapy has shown favorable survival in clinical trials for patients with advanced melanoma and NSCLC 39, 40, 41, 42, 43. However, the role of immune checkpoint inhibitors in the treatment of CNS cancers, including metastasis, is currently being defined,44, 45 and our current results provide further support for these agents in this context.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the immune system, tumor and the tumor microenvironment has been the focus of intense investigation—specifically the role of the PD‐1/PDL‐1 signaling axis,38 The efficacy of PD‐1 inhibition (i.e., nivolumab and pembrolizumab) as a monotherapy or in combination therapy has shown favorable survival in clinical trials for patients with advanced melanoma and NSCLC 39, 40, 41, 42, 43. However, the role of immune checkpoint inhibitors in the treatment of CNS cancers, including metastasis, is currently being defined,44, 45 and our current results provide further support for these agents in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy using antibodies targeting checkpoint proteins has become of increasing interest and a number of clinical trials using these antibodies for several different cancer types have shown clinical responses 22, 23, 24, 25, 26, 27, 28. However, studies with animal models and cancer patients have also shown that combining antibody blockade of the PD‐1/PD‐L1 axis with other forms of immunotherapy can lead to more meaningful clinical responses 32, 33, 34, 35.…”
Section: Discussionmentioning
confidence: 99%
“…Using a different PD‐1 blockade antibody, nivolumab, clinical efficacy was shown for patients with metastatic renal cell carcinoma and for patients with ovarian cancer 26, 27. Nivolumab also increased survival of patients with non‐squamous non‐small‐cell lung cancer that resisted prior chemotherapy 28. A meta‐analysis of clinical trials involving nivolumab‐based therapy for advanced melanoma showed that treatment prolonged patient progression‐free survival 29.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of activity of PD-1/PD-L1-directed agents has also been observed in patients who are never smokers and in patients with EGFR mutation-positive NSCLC [51, 52, 61]. It has been shown that NSCLC patients with tumors that have a high mutational burden have a greater probability of benefit from checkpoint inhibition [62].…”
Section: Post-alk Inhibitor Therapymentioning
confidence: 99%